Mechanical Performance of Actuators in an Active Orthosis for the Upper Extremities - Roland Wiegand; Bastian Schmitz; Christian Pylatiuk; Stefan Schulz (Journal of Robotics)
The aim of the project OrthoJacket is to develop a lightweight, portable, and active orthosis for the upper limps. The system consists of two special designed fluidic actuators which are used for supporting the elbow function and the internal rotation of the shoulder. A new design of flexible fluid actuator (FFA) is presented that enables more design options of attaching parts, as it is allowed by conventional actuators with a stationary centre of rotation. This advantage and the inherent flexibility and the low weight of this kind of actuator predestined them for the use in exoskeletons, orthoses, and prostheses. The actuator for the elbow generates a maximum torque of 32 Nm; the internal rotation is supported with 7 Nm. Both actuators support the movement with up to 100% of the necessary power. The shells for the arm and forearm are made of carbon reinforced structures in combination with inflatable cushions.